Diversity of potassium channels in human umbilical artery smooth muscle cells: a review of their roles in human umbilical artery contraction - Martín, Pedro (2014)
Through their control of cell membrane potential, potassium (K+) channels are among the best known regulators of vascular tone. This article discusses the expression and function of K+ channels in human umbilical artery smooth muscle cells (HUASMCs). We review the bibliographic reports and also present single-channel data recorded in freshly isolated cells. Electrophysiological properties of big conductance, voltage- and Ca2+-sensitive K+ channel and voltage-dependent K+ channels are clearly established in this vessel, where they are involved in contractile state regulation. Their role in the maintenance of membrane potential is an important control mechanism in the determination of the vessel diameter. Additionally, small conductance Ca2+-sensitive K+ channels, 2-pore domains K+ channels and inward rectifier K+ channels also appear to be present in HUASMCs, while intermediate conductance Ca2+-sensitive K+ channels and ATP-sensitive K+ channels could not be identified. In both cases, additional investigation is necessary to reach conclusive evidence of their expression and/or functional role in HUASMCs. Finally, we discuss the role of K+ channels in pregnancy-related pathologies like gestational diabetes and preeclampsia.